Protein substances of oat bran and their influence on conformational transformations in dough and bread from wheat flour - Shevchenko, Anastasiia; Litvynchuk (Vorontsova), Svitlana (My University, 2022)
The aim of the work was to determine the degree of completeness of protein substances of oat bran and its influence on conformational transformations in the structure of dough semi-finished products and bread made from wheat flour. Oat bran, its amino acid composition and influence on the content of protein substances in bread were investigated. Conformational transformations of structural elements in dough and bread were investigated by infrared spectroscopy in the near-infrared region. The content of essential amino acids in oat bran is significantly higher than in premium wheat flour. The limiting amino acid in wheat flour is lysine, the amino acid score of which is 0.44. In oat bran the limiting amino acid is methionine, the amino acid score of which is 1.14, and the amino acid score of lysine is much higher than in wheat flour – 1.62. The limiting amino acid in bread is lysine, the amino acid score of which is 0.46. With an increase in the percentage of replacement of wheat flour with oat bran, the amino acid score of lysine increased by 19.5–52.2%. This indicates that the protein of this raw material helps to increase the level of essential amino acids in bread, which enriches its protein profile. The obtained spectra of the dough samples after kneading showed that the introduction of oat bran does not cause conformational changes in the dough system, since not enough time passed for the interaction of the biopolymers of the raw materials. The infrared spectra of the dough at a wavelength of 2100 nm showed that the dietary fibers of oat bran delay the development of the gluten network, the structure of the protein matrix of the dough with bran will be less stable and more weakened than that of the control sample. The introduction of oat bran with a higher content of protein, dietary fiber and a complete amino acid profile into the recipe of wheat bread helps to improve the biological value of bread with this raw material. However, the deterioration of the development of the gluten framework of the dough, and therefore of the specific volume, porosity and dimensional stability of bread, requires the use of technological methods to minimize the negative impact of bran on the quality of finished bakery products.
Keywords: bread; oat bran; gluten; amino acid; кафедра технології хлібопекарських і кондитерських виробів; кафедра фізики та професійної безпеки